COPYRIGHT PROTECTION AS AN EFFORT TO INCREASE BRAND PREFERENCE FOR RABBANI ORIGINAL PRODUCTS USING SWOT ANALYSIS - Husna, Fauziah; Cecep Syafa'atul Barkah; Tetty Herawaty (MANABIS: Jurnal Manajemen dan Bisnis, 2023)
The purpose of this study is to determine strategies to increase brand preference for authentic Rabbani products through SWOT analysis. In determining the marketing strategy it is necessary to know the strengths, weaknesses, opportunities, and threats. The design used in this research is descriptive qualitative. The subject of this research is the owner of Rabbani Jatinangor. The research instrument used was interviewed. The results showed that the analysis of strengths consisted of having many product variants, good product quality, and comfortable use, having many branches abroad, competitive prices offered, and good service quality, while weaknesses consisted of product designs that were easily imitated by competitors, several outlets had land narrow parking, optimization of the shopee marketplace for several outlets is still lacking, promotions only focus on direct marketing and personal selling, the only product that is in great demand is instant hijab. Then the opportunity consists of offers of cooperation with television programs, school students who are interested in the Rabbani student ambassador program, have entered foreign markets, relations with several celebrities as brand ambassadors, there are Muslim holidays, and the thread consists of increasingly competitive Muslim clothing. tight, many counterfeit products at low prices on the market, many competitors use online marketing, fashion trends change rapidly, and competitors open stores in nearby locations. Based on the results of the Rabbani SWOT matrix analysis, it is in the growth-oriented quadrant I (growth). Due to the large number of counterfeit products that have an impact on consumers turning away from counterfeit products, a strategy that can be carried out by Rabbani is to protect the copyright of the Rabbani brand